Sistem Pengupahan Pekerja Pengelola Barang Bekas Dalam Tinjauan Hukum Ekonomi Syariah - Siska, Arda; Wiyos Rini Masykuroh, Yufi; Sumanto, Yusika (Kartika: Jurnal Studi Keislaman, 2025)
This study analyzes the wage system for scrap collectors in the context of Sharia economic law in Terusan Nunyai Subdistrict, Central Lampung Regency. Labor guidelines have not yet established clear wage standards for scrap collectors, who are part of the informal sector. Current wage practices still depend on verbal agreements between employers and workers without written contracts. The compatibility of the wage system with the principles of ijarah contracts in Islamic economic law was examined through a qualitative approach using field research methods. The results of the study show that the wage system for scrap workers does not fully meet the principles of fairness, clarity of object, and voluntary agreement that are important in ijarah contracts. Injustice and gharar, or uncertainty, can arise if it is unclear how wages, workloads, and payment times are determined. This contradicts sharia principles. To protect the rights of informal sector workers, this study recommends standardizing the wage system with reference to fairness in Islamic economic law.